Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/ped.13309
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric psoriasis: Should we be concerned with comorbidity? Cross‐sectional study

Abstract: Given the frequent association of pediatric psoriasis with many disorders, these comorbidities should be investigated and identified so that they can be taken into account in the management of psoriasis in order to avoid treatment failure. Regular follow up should be carried out in patients at risk of metabolic comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…36 The strength of recommendations and levels of evidence for psoriasis and obesity are summarized in Tables VI and VII. 11,12,25,27,[30][31][32][33][34][35]37,38…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…36 The strength of recommendations and levels of evidence for psoriasis and obesity are summarized in Tables VI and VII. 11,12,25,27,[30][31][32][33][34][35]37,38…”
Section: Psoriatic Arthritismentioning
confidence: 99%
“…Recently, a mutation in the interleukin 36 receptor antagonist gene leading to a defect in interleukin 36 antagonist was identified in generalized pustular psoriasis and acrodermatitis continua suppurativa supporting the view that it belongs to the autoinflammatory diseases group. 5 , 6 Pustulosis palmoplantaris is histopathologically and genetically different and rarely affects the periungual skin. 7 …”
Section: Clinical Characteristics Of Nail Psoriasismentioning
confidence: 99%
“…Carobbo et al [ 16 ] found hypertension, in the single-center study, in eight out of 60 patients (13% of the entire cohort). In contrast, in a cross-sectional study by Kelati et al [ 19 ] involving 84 children with psoriasis and comorbidities, no cases of arterial hypertension were detected. In the meta-analysis performed by Pietrzak et al [ 15 ], similarly, there was no difference in the systolic and diastolic blood pressure between the group of psoriatic children and the control group.…”
Section: Cardiovascular Diseasesmentioning
confidence: 75%